Ultrasound monitoring respiratory muscle rehabilitation training can promote the recovery of diaphragmatic function in traumatic spinal cord injury (TSCI) patients - Xinyu Zhang; Xiaobo Zhang; Dong Yang; Li Liu; Xiulin Huo; Zhuojun Deng (European Journal of Medical Research)
Abstract Background and objective Traumatic spinal cord injury (TSCI) often leads to respiratory dysfunction, in which the impaired diaphragm function is one of the main causes. Respiratory muscle rehabilitation training can be used to improve respiratory function, but its effect on diaphragm function has not been deeply investigated. This study employed ultrasound monitoring to assess how respiratory muscle rehabilitation training affects diaphragmatic function in TSCI patients. Methods In this prospective randomized controlled trial (RCT) study, 56 patients with spinal cord injury were randomly divided into experimental group and control group, 28 cases in each group. The experimental group received respiratory muscle rehabilitation training twice a day for 15 min each time; and the control group received only the usual care. The diaphragm thickness, diaphragm movement and diaphragm contraction speed of the two groups were measured by ultrasound before and after training. Results Compared to the control group, the experimental group had significant improvements. Diaphragm thickness increased from 2.05 ± 0.25 mm to 2.38 ± 0.30 mm in the experimental group (P < 0.001), while the control group changed minimally from 2.02 ± 0.22 mm to 2.05 ± 0.23 mm (P = 0.338). Diaphragm movement increased from 1.52 ± 0.20 mm to 1.85 ± 0.25 mm in the experimental group (P < 0.001), versus a small change from 1.50 ± 0.18 mm to 1.53 ± 0.20 mm in the control group (P = 0.315). Diaphragm contraction speed accelerated from 1.20 ± 0.15 cm/s to 1.45 ± 0.20 cm/s in the experimental group (P < 0.001), while the control group changed slightly from 1.18 ± 0.13 cm/s to 1.20 ± 0.15 cm/s (P = 0.380). Respiratory frequency decreased from 20.3 ± 3.4 times/min to 16.0 ± 2.5 times/min in the experimental group (P < 0.001), and the control group changed less from 19.5 ± 2.1 times/min to 18.2 ± 2.3 times/min (P = 0.070). Ventilator removal time was significantly reduced in the experimental group (14.1 ± 1.5 days) compared to the control group (20.2 ± 2.0 days, P = 0.002). Conclusion Respiratory muscle rehabilitation significantly enhances diaphragm function and respiratory parameters in spinal cord injury patients. Ultrasound monitoring effectively evaluates these improvements, providing a valuable, novel clinical approach for TSCI rehabilitation. While this preliminary RCT demonstrates positive outcomes, the sample size limitation (n = 56) and absence of long-term follow-up should be acknowledged. These aspects will be addressed through larger sample sizes and extended observation periods in subsequent research.